Efeito do óleo essencial de capim santo (Cymbopogon citratus) (Stapf) DC. (Poaceae) em Argulídeos (Crustacea, Branchiura): Argulus sp e Dolops discoidalis. - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
The increase in the number of fish farms in the national territory associated to the intensification of production, there have been outbreaks and high fish mortalities due to the diseases. One of the main obstacles is the occurrence of parasitic infestations, followed or not by the presence of opportunistic pathogens. Among these opportunistic pathogens are crustaceans, periodic ectoparasites of marine and sweet fish. Among the crustaceans, there is the subclass Branchiura, popularly called "fish lice" or Argulídeos, which compromises sanity in aquaculture, so its control is fundamental. However, the use of natural products (phytotherapics) has been gaining prominence in animal health, mainly because they are efficient bioactive substances in parasitic control. One of these plants with potential use in aquaculture is the holy grass (Cymbopogon citratus), the essential oil extracted from this plant is efficient in the control of bovine ectoparasites. This thesis studied the effects of the essential oil of C. citratus ( major components geranial, neral and mirceno) in the control of ectoparasites of fish belonging to the family Argulidae (Dolops discoidalis and Argulus sp), through the LC50-24h test with dosages 20 µg/L, 40 µg/L; 60 µg/L, 80 µg/L, 100 µg/L, 120 µg/L, 140 µg/L and 160 µg/L. The maximum mortality for the representatives of Argulus sp started from the concentration of 100 µg/L, while the maximum mortality of Dolops discoidalis started in the treatment of 80 µg/L. The Lethal Concentration (LC50-24h) for adult Argulus sp was 76,3μg / L and adult Dolops discoidalis was 59,3μg / L. It was observed that all mortality in the test (LC50-24h) occurred in the first hour. The essential oil of C. citratus was also tested (LC50-24h) in the ovipositions of argulids, in both the maximum mortality (100%) of the ovipositions started from the treatments of 140μg / L and 160μg / L. The Lethal Concentration (LC50-24h) for the ovipositions of Argulus sp and Dolops discoidalis were 99,7 μg / L and 99,3 μg / L, respectively. The parasite phase was important for the definition of the control concentration. In addition, studies are required to evaluate the effect on infected fish for the indication of this oil in aquaculture, since in this work, low concentrations of C. citratus O.E. CL were determined in the control of adult Argulids.
Keywords: Aquicultura; Fitoterápico; Sanidade; Óleos essenciais; CNPQ: GEOCIÊNCIAS; RECURSOS NATURAIS; RECURSOS NATURAIS, BIODIVERSIDADE E BIOPROSTECÇÃO NA AMAZÔNIA; SOCIEDADE, NATUREZA E DESENVOLVIMENTO